2013
DOI: 10.2106/jbjs.k.01558
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Obesity on the Outcome of Treatment of Lumbar Disc Herniation

Abstract: Obese patients realized less clinical benefit from both operative and nonoperative treatment of lumbar disc herniation. Surgery provided similar benefit over nonoperative treatment in obese and nonobese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
102
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(118 citation statements)
references
References 31 publications
9
102
0
7
Order By: Relevance
“…One limitation of the SPORT, and therefore this study, is the high crossover rate observed between the operative and nonoperative groups. However, because previous authors found consistencies between cohorts, the data have been combined into an as-treated analysis in many of the studies included in this review [3,5,6,8,9,11,[14][15][16][17][18]. Also, the 8-year followup rate was 63% of the initial subjects, and baseline demographics tended to be favorable to a better outcome in both the surgical and nonoperative groups [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One limitation of the SPORT, and therefore this study, is the high crossover rate observed between the operative and nonoperative groups. However, because previous authors found consistencies between cohorts, the data have been combined into an as-treated analysis in many of the studies included in this review [3,5,6,8,9,11,[14][15][16][17][18]. Also, the 8-year followup rate was 63% of the initial subjects, and baseline demographics tended to be favorable to a better outcome in both the surgical and nonoperative groups [10].…”
Section: Discussionmentioning
confidence: 99%
“…Search criteria included ''SPORT'' AND ''disc'' AND ''Spine Patients Outcomes Research Trial,'' which returned 36 articles. Of these, we identified 11 articles that analyzed subgroups of the SPORT patients with IDH [3,5,6,8,9,11,[14][15][16][17][18] (Table 1). A listing of SPORT-related Table 1.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that obesity has been associated with unfavorable surgical outcomes such as longer operative times, greater operative blood loss, and a higher rate of revision for patients having spinal surgery [10,14,31,32,35,39]. However, other studies did not find significant differences regarding surgical outcome and complications between patients who were obese or not obese [2,5,9,26].…”
Section: Introductionmentioning
confidence: 99%
“…This was true in both the operative (lumbar microdiscectomy) and non-operative arms. Additionally, obese patients that were managed operatively demonstrated significantly less improvement and lower final follow up values in the Sciatica Bothersomeness and Low Back Pain Bothersomeness Indices [42]. Though seemingly at odds with other clinical studies [12,20,[34][35][36], this as-treated analysis of the SPORT study has the benefit of a prospective design with large samples from multiple geographic locals and medical centers and long-term follow up which affords favorable generalizability of its results to true values expected in clinical practice.…”
Section: Discussionmentioning
confidence: 90%